2019
DOI: 10.1002/asia.201901242
|View full text |Cite
|
Sign up to set email alerts
|

Sodalite‐type Cu‐based Three‐dimensional Metal–Organic Framework for Efficient Oxygen Reduction Reaction

Abstract: Inspired by copper-based oxygen reduction biocatalysts, we have studied the electrocatalytic behavioro fa Cu-based MOF (Cu-BTT) for oxygen reduction reaction( ORR) in alkaline medium. This catalyst reducest he oxygen at the onset (E onset )a nd half-wavep otential (E 1/2 )o f0 .9 40 Va nd 0.778 V, respectively.T he high halfway potential supports the good activity of Cu-BTT MOF.T he high ORR catalytic activity can be interpreted by the presence of nitrogen-rich ligand (tetrazole) and the generation of nascent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The MOF showed an onset and half-wave potential of 0.94 and 0.78 V vs RHE, a number of transferred electrons of approximately 4, exceptional methanol crossover (no changes after addition of 1 M MeOH), and good cycling stability (84% of current retained after 12 h), with no changes to the porous morphology detected after ORR. The high activity was attributed to the formation of nascent copper(I) moiety from copper (II), which is also surrounded by nitrogen-rich tetrazole moiety, thus increasing ORR activity (Mani et al, 2019). Kim et al reported the use of a Cu(II)-MOF-derived Cu@CuO 2 core-shell nanocatalyst obtained via reduction with borohydride as an electrocatalyst for the ORR in alkaline medium (0.1 M KOH).…”
Section: Transition Metal Alloys For Orrmentioning
confidence: 99%
“…The MOF showed an onset and half-wave potential of 0.94 and 0.78 V vs RHE, a number of transferred electrons of approximately 4, exceptional methanol crossover (no changes after addition of 1 M MeOH), and good cycling stability (84% of current retained after 12 h), with no changes to the porous morphology detected after ORR. The high activity was attributed to the formation of nascent copper(I) moiety from copper (II), which is also surrounded by nitrogen-rich tetrazole moiety, thus increasing ORR activity (Mani et al, 2019). Kim et al reported the use of a Cu(II)-MOF-derived Cu@CuO 2 core-shell nanocatalyst obtained via reduction with borohydride as an electrocatalyst for the ORR in alkaline medium (0.1 M KOH).…”
Section: Transition Metal Alloys For Orrmentioning
confidence: 99%
“…As shown in Figures S14 and S15, slight changes in the morphology of Cu-CP were noticed, which might be due to the presence of the Vulcan carbon and Nafion, used as additive and binder, respectively, at the time of the ink formation. While performing XPS experiment (Figure 7a,7b), shifting in peak position of the Cu 2p spectrum was noticed (Figure 7b), which may be ascribed to the change in the oxidation state of copper 43 during ORR experiment. The fluorine and sulfur peaks were also present in the survey spectrum of the Cu-CP (after ADT sample) which arose from the Nafion binder solution (Figure 7a).…”
Section: ■ Computational Detailsmentioning
confidence: 99%
“…The structural changes that occur during the pyrolysis process are difficult to understand, which further leads to ambiguity in identification of the active site. The reports on non-pyrolyzed, pristine CP for biomimetic ORR application remain rare, and therefore, it creates a limitless scope for further developments. , …”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the low-cost and N-riched precursor is the key to prepare high-performance FeÀ NÀ C catalysts for ORR. [21] Polybenzimidazoles (PBIs) are heterocyclic polymers containing benzimidazole moieties in their backbone. Among PBI structure derivatives, poly (2, 5-benzimidazole) (ABPBI) has attracted much attention.…”
Section: Introductionmentioning
confidence: 99%